Languages in Conflict Situations in the Context of the Law of Ukraine “On Education” (2017) - Csernicsko Istvan; Csernicskó István; Черничко Степан (Harrassowitz Verlag, 2021)
Abstract. Following the dissolution of the Soviet Union, Ukrainian nation building was aided by the system of institutions inherited from the USSR (relatively clear-defined internal and external borders, a parliament, ministries, representation in the UN, etc.) but, at the same time, made difficult by the Russian community living in Ukraine, which became a minority overnight (BRUBAKER 1996, 17). The presence of the sizeable Russian community has been felt primarily in the Ukrainian-Russian language struggles. Researchers (STEPANENKO 2003, 121; PAVLENKO 2008, 275) and specialists at international organisations (e.g., Opinion 2011, 7; 2017; UN 2014) have repeatedly pointed out that the question of languages is heavily politicised in Ukraine, and that the fact that it is not clearly settled can lead to the emergence of language ideologies as well as to conflicts between ethnic groups and languages.
Keywords: conflict situation; Ukraine; education